2012
DOI: 10.1254/jphs.12r04cp
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Fetal Cardiac Gene Program

Abstract: Abstract. Reactivation of the fetal cardiac gene program in adults is a reliable marker of cardiac hypertrophy and heart failure. Normally, genes within this group are expressed in the fetal ventricles during development, but are silent after birth. However, their expression is re-induced in the ventricular myocardium in response to various cardiovascular diseases, and potentially plays an important role in the pathological process of cardiac remodeling. Thus, analysis of the molecular mechanisms that govern t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 52 publications
1
60
0
1
Order By: Relevance
“…The immature myocardium is generally known to have electrophysiological and contractile properties different from those of the adult myocardium (2,5,6). In the case of the mouse heart, the beating rate increases during pre-and postnatal development; the heart rate of the fetal mouse reaches 200 on the 16th fetal day (7), is about 320 on the day of birth, and reaches the adult level of about 700 at 2 weeks after birth (1,8).…”
Section: Introductionmentioning
confidence: 99%
“…The immature myocardium is generally known to have electrophysiological and contractile properties different from those of the adult myocardium (2,5,6). In the case of the mouse heart, the beating rate increases during pre-and postnatal development; the heart rate of the fetal mouse reaches 200 on the 16th fetal day (7), is about 320 on the day of birth, and reaches the adult level of about 700 at 2 weeks after birth (1,8).…”
Section: Introductionmentioning
confidence: 99%
“…We investigated whether changes in these transcription factor interactions were associated with changes in the expression of fetal genes, such as ANP, BNP, and skeletal α-actin, which are regulated by REST and mSin3A [20,53]. Transcript levels of ANP and β-myosin heavy chain were not different between groups, but BNP and skeletal α-actin were significantly reduced in db hearts independent of exercise (Figure  10).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, lowering O-GlcNAc by intensive swim training [43,44] has been proposed as a mechanism by which exercise benefits the diabetic heart, and exercise lowers both the O-GlcNAc modification of the SP1 transcription factor and the OGT enzyme. O-GlcNAc directly mediates the expression of fetal genes in response to hypertrophic stimuli [29], and O-GlcNAc modifies mSin3A and HDAC1 [35], which regulate cardiac hypertrophy [20,58]. Previously, we have shown that exercise lowers the O-GlcNAc modification of the OGT enzyme [32], and others have shown that exercise lowers O-GlcNAcylation of the SP1 transcription factor [43].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions the adult heart generates 70% of its ATP through fatty acid oxidation and 30% through glucose and lactate metabolism [8]. Heart failure is not only characterized by modified ventricular mass, but also by a switch to the fetal gene expression program causing altered substrate utilization [9]. The fetal heart develops in an environment low in oxygen that preferentially uses glucose as a substrate for energy [10, 11].…”
Section: Introductionmentioning
confidence: 99%